Fabrication of an effusive molecular beam instrument for surface reaction kinetics - CO oxidation and NO reduction on Pd(111) surfaces - Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Catalysis Letters, 2007)
A simple molecular beam instrument (MBI) was fabricated for measuring the fundamental parameters in catalysis such as, sticking coefficient, transient and steady state kinetics and reaction mechanism of gas/vapor phase reactions on metal surfaces. Important aspects of MBI fabrication are given in detail. Nitric oxide (NO) decomposition and NO reduction with carbon monoxide (CO) on Pd(111) surfaces were studied. Interesting results were observed for the above reactions and they support the efficiency of the MBI to derive the fundamental parameters of adsorption and catalysis. Sustenance of CO oxidation at 400 K is dependent mostly on the absence of CO-poisoning; apparently, CO + O recombination is the rate determining step <= 400 K. NO adsorption measurements on Pd(111) surface clearly indicating a typical precursor kinetics. Displacement of the chemisorbed CO by NO on Pd(111) surfaces was observed directly with NO + CO beams in the transient kinetics. It is also relatively easy to identify the rate-determining step directly from the MBI data and the same was demonstrated for the above reactions.
Keywords: carbon monoxide; catalysis; kinetics; molecular beam; nitric oxide; Pd(111)

Electronic decoupling of surface layers from bulk and its influence in oxidation catalysis: a molecular beam study - Thirunavukkarasu, Kandasamy; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Applied Surface Science, 2009)
Interactions between oxygen and Pd-surfaces have important implications, especially towards oxidation reactions, and influence of subsurface oxygen to oxidation reactions is the focus of the present study. In our efforts to understand the above aspects, CO oxidation reactions have been carried out with mixed molecular beam (MB), consisting CO and O(2), on Pd(1 1 1) surfaces under a wide variety of conditions (T = 400-900 K, CO: O(2) = 7: 1 to 1: 10). A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd subsurface layers, and its significant influence towards CO oxidation at high temperatures (>= 600 K). Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(O-sub)), above which the reactive CO adsorption occurs on the surface and simultaneous CO(2) production begins. There is also a significant time delay (G) observed between the onset of oxygen adsorption and CO adsorption (and CO(2) production). Above studies suggest an electronic decoupling of oxygen covered surface and subsurface layers, which is slightly oxidized, from the metallic bulk, which induces CO adsorption at high temperatures and simultaneous oxidation to CO(2). (C) 2009 Elsevier B.V. All rights reserved.
2nd International Conference on Physics at Surfaces and Interfaces (PSI2009), Puri, INDIA, FEB 23-27, 2009
Keywords: Electronic decoupling; heterogeneous catalysis; molecular beam; Oxidation; Pd(111); Subsurface diffusion